A Framework of Simulation and Gaming for Enhancing Community Resilience Against Large-Scale Earthquakes: Application for Achievements in Japan. (April 2020) - Toyoda, Yusuke
Background. The significance of mutual-help in communities for disaster management is a fundamental important concept. However, the current societal state does not reflect this lesson.S&G (Simulation and Gaming) has the potential to overcome the challenges faced in promoting community-based disaster management. No scientific research is currently present that reviews their achievements in Japan. Aim. This paper analyzes the current achievements of S&G in enhancingcommunity resilience againstlarge-scale earthquakes inJapan . Method. The paper clarifies the theoretical advantages of S&G in enhancing community resilience in coping and adaptive capacity plus proposes a conceptual contribution framework of S&G in improving community resilience. Based on this framework, the paper analyzes some major games that tackle community resilience against earthquakes in Japan. Results. The paper demonstrates the achievements through the S&G spectrum that stresses the disastrous experience with specific resilience views on one side, while decision making for critical reflection from other players with more comprehensive resilience views on the other side. Conclusion. The paper showcases the current S&G achievements in enhancing community resilience against large-scale earthquakes in Japan using the proposed framework, which can be utilized by other disaster-prone countries to develop and evaluate applications of S&G for increasing community resilience against earthquakes.